2007
DOI: 10.3748/wjg.v13.i7.1074
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C risk assessment, testing and referral for treatment in urban primary care: Role of race and ethnicity

Abstract: Racial differences exist with respect to HCV risk factor ascertainment and testing, (3) Minority patients, positive for HCV, are less likely to be referred for subspecialty care and treatment. Overall, minorities are less likely to be tested for HCV than whites in the presence of a known risk factor. INTRODUCTIONSeveral studies have suggested that hepatitis C (HBV) manage-ment is suboptimal in primary care settings [1][2][3][4][5] . In fact, only 59% of primary care physicians (PCPs) reported asking patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 10 publications
5
36
2
Order By: Relevance
“…Immigration status, race and language barriers have been identified as factors that impede access to HCV-related health care in many developed countries [10,11]. Given the heavy burden of HCV infection in immigrants living in Canada and other developed regions of the world, these factors need to be considered to ensure that immigrant populations receive adequate care [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immigration status, race and language barriers have been identified as factors that impede access to HCV-related health care in many developed countries [10,11]. Given the heavy burden of HCV infection in immigrants living in Canada and other developed regions of the world, these factors need to be considered to ensure that immigrant populations receive adequate care [15].…”
Section: Discussionmentioning
confidence: 99%
“…Communication issues resulting from physician-patient language discordance are known to influence health care satisfaction [5][6][7][8]. Racial and ethnic disparities concerning access to health care are well recognized [9][10][11]. Socioeconomic status is another potential obstacle to health care delivery, even in countries with publicly funded universal health care systems [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A chart review of more than 4,000 medical charts from 4 clinic sites in Philadelphia revealed that only 32% of African Americans and 40% of Hispanics who had tested positive for HCV had documented referral to a specialist for interferon and ribavirin therapy compared to 71% of whites who tested positive for HCV. 28 Another study from Los Angeles showed that even though Hispanics were more likely to be eligible for treatment, they were less frequently initiated on therapy and more likely to prematurely end treatment. 25 Disparities in rates of referral for HCV therapy are further compounded by racial differences in response rate to interferon-based therapy.…”
Section: Racial Disparities In the Treatment Of Liver Diseasementioning
confidence: 99%
“…What is troublesome is that even in well-identifi ed high-risk populations, documentation of HCV infection is infrequent and referrals for therapy are rare. Trooskin et al [ 43 ], in the recent publication of their study designed to determine rates of HCV risk factor ascertainment, testing, and referral from four primary care sites in Philadelphia, reported on the effect of race and ethnicity. They found that in urban primary care, documentation of an HCV risk factor history was uncommon.…”
Section: Risk Factor Ascertainment Testing and Referral For Treatmentmentioning
confidence: 98%